Implementasi Model Pembelajaran Kooperatif Tipe NHT dalam Meningkatkan Kerjasama Antar Siswa pada Mata Pelajaran Bahasa Indonesia Kelas III SDN 12 Mataram - Safirah Ahdiatu; Ika Rachmayani; Dika Areka (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to describe the implementation of the Numbered Heads Together (NHT) cooperative learning model in improving students’ cooperation in Indonesian language learning for third-grade students at SDN 12 Mataram. The background of this study is the lack of optimal student cooperation during the learning process, particularly in group discussions. This research employed a qualitative approach with a descriptive method. The research subjects were the teacher and 28 third-grade students of SDN 12 Mataram in the 2024/2025 academic year. Data were collected through observation, interviews, and documentation. The results indicate that the implementation of the NHT cooperative learning model was able to create a more active, participatory, and collaborative learning environment. Students were directly involved in group discussions, able to exchange ideas, and demonstrated mutual respect and cooperation in completing tasks. The teacher acted as a facilitator who guided the discussion process and provided motivation. Overall, the application of the NHT model in Indonesian language learning has been proven to enhance cooperation among third-grade students at SDN 12 Mataram.